Aproximación a Como calquera outro día (1962) de Camilo Gonsar - BERMÚDEZ MONTES, M.ª Teresa (Madrygal. Revista de Estudios Gallegos, 2010)
This paper seeks to show the main characteristics of Como calquera outro día (1962), Galician writer Camilo Gonsar’s first novel. Philosophical thought, realism and autobiographical fiction are allied to made up the generational portrait of the young people at that time, the “50’s Generation”, under the Franco’s regime.
Keywords: Galician Narrative XXth Century; Gonsar; Como calquera outro día; 50’s generation